Histopathological changes of ejaculated embryos of the ejaculation Confederation - Dunya Abdullah; Intesar Al-Knani; Ahlam Al-Taee (College of Education for Pure Sciences, 2007)
ABSTRACT This study was conducted to elucidate the histopathologicl changes in fetuses of ewe infected with Toxoplasma gondii , the results revealed that histopathological lesions occure in brain , liver , heart muscle ,lung , eye , pancreas and spleen . represented by preivascaular lymphostic cuffing in blood vesseles,parasitic encephalomylitis in brain , necrotizing hepatitis , lymphocytic myocarditis , interstitial pneumonia in lung and choroidreticulitis in eye.As well as neccrotizing pancreatitis and invasion of large amount of tachyzoit has been seen .In spleen localization of tachyzoit and tissue cyst in and out the lymphocytic cell in addition to thickness of spleen trabculae have been seen .الخلاصةتضمنت هذه الدراسة معرفة التغیرات المرضیة النسجیة فی أجنة النعاج المجهضة الخمجة طبیعیا بالمقوسة الکوندیة ، وأظهرت النتائج وجود آفات مرضیة نسجیة فی کل من الدماغ والکبد وعضلة القلب والرئة والعین والبنکریاس والطحال تمثلت بتکفف الخلایا اللمفیة حول الأوعیة الدمویة الدماغیة مع وجود التهاب السحایا والدماغ الطفیلی parasitic encephalomylitis فی الدماغ ، التهاب الکبد النخری necrotizing hepatitis ،التهاب عضل القلب اللمفی lymphocytic myocarditis وذات الرئة الخلالیة interstitial pneumonia والتهاب الشبکیة المشیمی choroidreticulitis ، فضلا عن ظهور آفات فی البنکریاس تمثلت بالتهاب البنکریاس النخری Necrotizing pancreatitis مع غزو أعداد کبیرة من الحوینات السریعة التکاثر لنسیج البنکریاس ، فی حین اظهر الفحص النسجی للطحال تموضع أعداد کبیرة من الحوینات السریعة التکاثر والأکیاس النسیجیة داخل وخارج الخلایا اللمفیة ، فضلا عن ظهور تثخن فی الحویجزات الطحالیة .